The construction of a geography of the soul based on the contribution of archetypal psychology - da Silva, Rafael Gonçalves; Ferraz, Maíra Kahl [UNESP] (Universidade Federal de Goias, 2024)
Since the systematization of geographic science, certain aspects of human life were no longer incorporated into its conception. The soul is one of them. The current of humanist geography, using a phenomenological philosophy, intends to overcome a Cartesian logic, for this purpose it appropriates subjective aspects that were previously disregarded. In this sense, authors such as Dardel and Tuan will be exemplified. Still, there is no connection between geography and the soul. Therefore, starting from the contributions of archetypal psychology conceptualized by James Hillman, based on Jung’s analytical psychology, we will reflect on the contribution of this thought to geography. In this little explored interconnection, it is possible to construct a geography of the soul. This would be a perspective on communicating with an animated world. Its objective would be the deformation and construction of images, making all contact with the world an imaginative archetypal experience.
La construcción de una geografía del alma a partir del aporte de la psicología arquetípica
A construção de uma geografia da alma a partir da contribuição da psicologia arquetípica
Keywords: Archetypal psychology; Archetype; Image; Imagination; James Hillman